An Overview on RAM Memories in QCA Technology - Javad Chaharlang; Mohammad Mosleh (Majlesi Journal of Electrical Engineering)
Quantum-dot Cellular Automata (QCA) is a computational technology that can be used to construct nanoscale circuits. Nowadays, this technology is a good alternative for CMOS technology due to features such as high speed, low occupied area and low power consumption. Mmemory is utilized as one of the basic elements in digital circuit design hence the design and optimization of high-speed RAM memory cells have become one of the most attractive research areas; in the realm of QCA. In this paper, we present a comprehensive investigation on RAM memories. For this purpose, the proposed schemes in terms of functionality, the number of cell consumption, and latency are implemented and compared using QCA Designer software. The results show that some of the proposed schemes show better performance in terms of parameters such as occupied area and delay. Nevertheless, they are still suffering from less stability; hence introducing an optimum scheme is infeasible.